Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

For the functions [tex]\( f(x) = 4x - 4 \)[/tex] and [tex]\( g(x) = 5x - 5 \)[/tex], find [tex]\( (g \circ f)(x) \)[/tex].

Sagot :

To find the composition of the functions [tex]\( f \)[/tex] and [tex]\( g \)[/tex], which is denoted as [tex]\( (g \circ f)(x) \)[/tex], we need to evaluate [tex]\( g(f(x)) \)[/tex]. Here are the given functions:

[tex]\[ f(x) = 4x - 4 \][/tex]

[tex]\[ g(x) = 5x - 5 \][/tex]

Now, let's find the composition step-by-step:

1. First, find [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = 4x - 4 \][/tex]

2. Next, substitute [tex]\( f(x) \)[/tex] into [tex]\( g \)[/tex]:
We want [tex]\( g(f(x)) \)[/tex], so we replace [tex]\( x \)[/tex] in the function [tex]\( g(x) \)[/tex] with [tex]\( f(x) \)[/tex]. Thus,
[tex]\[ g(f(x)) = g(4x - 4) \][/tex]

3. Evaluate [tex]\( g \)[/tex] at [tex]\( 4x - 4 \)[/tex]:
Recall the definition of [tex]\( g \)[/tex]:
[tex]\[ g(x) = 5x - 5 \][/tex]
Therefore, to find [tex]\( g(4x - 4) \)[/tex]:
[tex]\[ g(4x - 4) = 5(4x - 4) - 5 \][/tex]

4. Simplify the expression:
[tex]\[ g(4x - 4) = 5(4x - 4) - 5 \][/tex]
First, distribute the 5:
[tex]\[ g(4x - 4) = 20x - 20 - 5 \][/tex]
Combine like terms:
[tex]\[ g(4x - 4) = 20x - 25 \][/tex]

Therefore, the composition of the functions [tex]\( (g \circ f)(x) \)[/tex] is:

[tex]\[ (g \circ f)(x) = 20x - 25 \][/tex]